Түлшээ үржүүлэн шатаах хурдан реакторын нейтроны тоог нэмэгдүүлэх боломжууд - Одмаа (Scientific transaction of the National University of Mongolia. Physics, 2023)
The breed-and-burn fast reactor utilizes depleted or natural uranium fuel and the fissile isotopes generate from fertile isotopes while the fissile ones burn. So, it has an advanced nuclear reactor with technological advantages to utilize uranium resources effectively as well as to reduce the amount of spent nuclear fuel. The integration of neutron number in a reactor core is determined by the difference between the total number of produced and absorbed neutrons, including lost neutrons in a core during burnup. While the neutron balance is high, the fuel breeding process works effectively. The objective of the research work is to find ways to increase the neutron balance in a reactor core. In the present work, the effect of some design parameters such as pin pitch, cladding thickness and density on neutron balance was studied for infinite one fuel cells with different materials.